1977
DOI: 10.1111/j.1476-5381.1977.tb07721.x
|View full text |Cite
|
Sign up to set email alerts
|

CARDIOVASCULAR EFFECTS OF Δ9‐TETRAHYDROCANNABINOL IN CONSCIOUS AND ANAESTHETIZED DOGS

Abstract: I Temporal effects of A9-tetrahydrocannabinol (THC) on heart rate and blood pressure in conscious dogs were compared to those in anaesthetized dogs. 3 In conscious dogs, THC in doses of 0.25 and 0.1 mg/kg resulted in maximal heart rate reductions of 48 and 41%, respectively, and in no significant change in blood pressure. 3 In anaesthetized animals THC in doses of 0.5 and 0.25 mg/kg caused a peak reduction in heart rate of 38 and 34%, and of blood pressure of 24 and 8%, respectively. 4 The results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Solowij et al [42] reported a significant increase in blood pressure in human subjects who inhaled 8 mg of ∆ 9 -THC by vaporization, which would equal an intake of approximately 0.1 mg/kg bw assuming a body weight of 70 kg. In a study by Friedman et al [43], the authors have found, that a total of approximately 0.25 mg/kg (about 0.1 mg/kg bw) of ∆ 9 -THC administered intravenously to dogs had no significant effect on blood pressure. Converting this dose into an inhaled dose for humans by considering an uncertainty factor of 100 and bioavailability for inhalation of 37% would yield an estimated inhalation dose of approximately 0.007 mg/kg bw of ∆ 9 -THC in humans.…”
Section: Dose-response Modeling Of Cbd and ∆ 9 -Thcmentioning
confidence: 98%
“…Solowij et al [42] reported a significant increase in blood pressure in human subjects who inhaled 8 mg of ∆ 9 -THC by vaporization, which would equal an intake of approximately 0.1 mg/kg bw assuming a body weight of 70 kg. In a study by Friedman et al [43], the authors have found, that a total of approximately 0.25 mg/kg (about 0.1 mg/kg bw) of ∆ 9 -THC administered intravenously to dogs had no significant effect on blood pressure. Converting this dose into an inhaled dose for humans by considering an uncertainty factor of 100 and bioavailability for inhalation of 37% would yield an estimated inhalation dose of approximately 0.007 mg/kg bw of ∆ 9 -THC in humans.…”
Section: Dose-response Modeling Of Cbd and ∆ 9 -Thcmentioning
confidence: 98%
“…Finally, there are substantial interspecies differences in the physiologic changes with THC administration, which limits the ability to extrapolate the results from animal studies to humans. For example, THC has been shown to reliably cause tachycardia and postural hypotension in humans regardless of the route of administration 27 but causes bradycardia in anesthetized dogs 28,29 and cats 30 as well as bradycardia and hypertension in rats. 31 THC administration also results in bronchodilation in humans 27,32 but causes a vagally mediated increase in lung resistance in dogs 29 and marked respiratory depression in cats.…”
Section: Physiologymentioning
confidence: 99%
“…One of the most consistent acute effects of cannabis administration in humans is tachycardia. 28 One study showed that cannabis-naive tobacco smokers with stable angina developed angina symptoms with exercise significantly faster after smoking cannabis. 34 Another study noted a fivefold increased risk of myocardial infarction (MI) in the first hour following cannabis smoking compared to a 24-fold increased risk of MI in the hour following cocaine ingestion.…”
Section: Acute Effectsmentioning
confidence: 99%